#### Answer

True

#### Work Step by Step

We check the supposed solution:
$$0 = x^2 +3x \\ 0 = x(x+3) \\ x=0,-3$$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

True

We check the supposed solution:
$$0 = x^2 +3x \\ 0 = x(x+3) \\ x=0,-3$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.